POLLUTING FACTORS IN RUBBER PLANTS THAT INTERFERE WITH HEALTH - Ferly Oktriyedi; Irfannuddin Irfannuddin; Ngudiantoro Ngudiantoro; M. Hatta Dahlan (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Production of natural rubber can have a detrimental effect on health. Hazardous pollution products from natural rubber industry are ammonia and sulfides which can be in the form of gas, solid/rubber crump, and liquid waste. These pollutants occur due to sub-standard PRPM management processes and the use of non-recommended clotting agents such as sulfuric acid, alum potassium, and Triple Super Phosphate (TSP) fertilizer. The natural rubber management process also uses machines that cause noise pollution. The impact of health problems that can occur contact dermatitis, hearing loss, respiratory diseases, and pulmonary parenchyma, and eye irritation.